(untitled) (Annals of Medical Research, 2021)
Aim: We aimed to investigate the relationship between oxidative parameters- total oxidant status (TOS), total antioxidant capacity (TAC), and oxidative stress index (OSI)- and EFT in patients with CSX. Without clinically significant coronary artery disease, cardiac syndrome X (CSX) is characterized by cardiac ischemia, and chest pain. However, there is some evidence about increased oxidative stress in CSX patients; the relationship between oxidative stress parameters and epicardial fat thickness (EFT) is not well established in this population. Material and Methods: One hundred and twenty-two patients with normal coronary arteries (73 female, 49 males, mean age 56.71 ± 10.69 years) were enrolled in the study. The study population was divided into two groups according to their OSI. Oxidative stress index below the median was defined as the OSI low group and equal or higher than the median was defined as the OSI high group.Results: EFT was higher in the high OSI group than the low OSI group (6 (3.9 – 8.9) vs. 5.4 (0.56 – 7.2), p= 0.032). In bivariate correlation analysis EFT was positively correlated with OSI and TOS (r=0.242, p=0.036 and r=0.234, p=0.025 respectively). In binary logistic regression analysis, EFT was found to be an independent predictor of OSI.Conclusion: In our study, EFT was independently associated with OSI in CSX patients. This finding suggests that EFT may be a marker of increased oxidative stress in CSX.